The Maintained Discharge of Rat Retinal Ganglion Cells - Freeman, Daniel K. (2008)
Action potentials were recorded from rat retinal ganglion cell fibers in the presence of a uniform field and the maintained discharge pattern was characterized. Spike trains recorded under ketamine/xylazine anesthesia were generally stationary, while those recorded under urethane anesthesia often showed slow, undriven, quasi-periodic fluctuations in firing rate. In light of these non-stationarities, interspike interval distributions and power spectral densities are reported for data collected primarily under ketamine/xylazine. The majority of cells had multi-modal interval distributions, with the first peak in the range of 25.0–38.5ms and the subsequent peaks occurring at integer multiples of the first peak. Cells with unimodal distributions were fit well by a gamma distribution function. Interval and spike count statistics showed that ON cells tended to fire faster than OFF cells and that cells with higher rates fired in a more regular manner, with the coefficient of variation covering a wide range of values across all cells (0.43–0.97). Both ON and OFF cells show serial correlations between adjacent interspike intervals, while ON cells also showed 2(nd) order correlations. Cells with multi-modal interval distribution showed a strong peak at high frequencies in the power spectra in the range of 28.9–41.4Hz. Oscillations were present under both anesthetic conditions and persisted in the dark at a slightly lower frequency, implying that the oscillations are generated independent of any light stimulus but can be modulated by light level. The oscillation frequency varied slightly between cells of the same type and in the same eye, suggesting that multiple oscillatory generating mechanisms exist within the retina. Cells with high frequency oscillations were described well by an integrate-and-fire model with the input consisting of Gaussian noise plus a sinusoid where the phase was jittered randomly to account for the bandwidth present in the oscillations.